Are the Triple Bottom Line and Green Accounting Supporting Corporate Performance? - Siti Nur Syakbandiyah; Yvonne Augustine Sudibyo (Technium Social Sciences Journal, 2025)
The objective of this research is to analyze “Are the Triple Bottom Line and green accounting support Corporate performance?”. This research was conducted using quantitative methods. The data used in this study is secondary data obtained from Indonesia Stock Exchange or the official Corporate website. The population used in this study were all companies in all sectors listed on Indonesia Stock Exchange during 2017-2021 with balanced data types. The data used was purposive sampling method with the result that 231 observation were selected in this research. The statistical method used is Panel Data Analysis. The result of this research, it shows that Triple Bottom Line in economics and environmental aspects have negative affect on the Corporate performance, but in social aspects has positive affect on the Corporate performance. The result of this study also state that green accounting has negative affect on the Corporate performance.